2016
DOI: 10.1371/journal.pone.0156130
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pelvic Inflammation Diminished Ovarian Reserve as Indicated by Serum Anti Mülerrian Hormone

Abstract: ObjectiveTo explore the potential damaging effect of chronic pelvic inflammation on ovarian reserve.DesignCase-control study.PatientsA total of 122 women with bilateral tubal occlusion, diagnosed by hysterosalipingography (HSG) and 217 women with normal fallopians were recruited.MeasurementsSerum anti-Mullerian hormone (AMH), basic follicle-stimulating hormone (FSH), luteining hormone (LH), estradiol (E2), and testosterone (T) were measured; and antral follicle counts (AFCs) were recorded.ResultsSignificantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
13
0
5
Order By: Relevance
“…During inflammatory processes activation of phosphoinositol 3 kinase (PI3K) results in conversion of phosphoinositol diphosphate to phosphoinositol triphosphate, with activation of protein kinase B (PKB, also known as AKT), which happens to be the pathway by which quiescent primordial follicles are activated to leave the resting pool and embark on development to ultimate atresia or ovulation . This observation seems to have clinical relevance because women with chronic pelvic inflammation experience depletion of the ovarian reserve (Cui et al, 2016). Depletion of primordial follicles not only shortens reproductive lifespan, but also may affect fertility at normal reproductive age.…”
Section: Inflammation Depletes the Pool Of Primordial Follicles (Ovarmentioning
confidence: 98%
“…During inflammatory processes activation of phosphoinositol 3 kinase (PI3K) results in conversion of phosphoinositol diphosphate to phosphoinositol triphosphate, with activation of protein kinase B (PKB, also known as AKT), which happens to be the pathway by which quiescent primordial follicles are activated to leave the resting pool and embark on development to ultimate atresia or ovulation . This observation seems to have clinical relevance because women with chronic pelvic inflammation experience depletion of the ovarian reserve (Cui et al, 2016). Depletion of primordial follicles not only shortens reproductive lifespan, but also may affect fertility at normal reproductive age.…”
Section: Inflammation Depletes the Pool Of Primordial Follicles (Ovarmentioning
confidence: 98%
“…In addition to the tissue destruction by mechanical needle insertion, pathophysiological mechanisms may also include the consequences of inflammatory responses to multiple needle entries supported by the previous data showed deleterious effect of chronic inflammation on the ovarian reserve (28). There are some studies published in the literature that showed elevated serum testosterone levels and insulin resistance following ovarian stimulation (29,30).…”
Section: Discussionmentioning
confidence: 84%
“…Це порушує анатомічне взаєморозміщення і здатне згодом підтримувати запальний процес (Brunha� �.C. et al, 2015;Cui L. et al, 2016;Зиганшин А.М., Мудров В.А., 2019;Huang C.-C. et al, 2019). Оклюзія фаллопієвих труб є найчастішим ускладненням ЗЗОМТ, що викликає 42,3% жіночого безпліддя (Cui L. et al, 2016).…”
Section: визначення та етіопатогенезunclassified